Adaptive disturbance rejection for course tracking of marine vessels under actuator constraint. (May 2020) - Hu, Xin; Wei, Xinjiang; Han, Jian; Zhang, Qiang
Abstract: This paper addresses the problem of adaptive disturbance rejection for the course tracking of marine vessels with unknown motion model parameters including the control coefficient and marine environmental disturbances under actuator constraint. An adaptive disturbance estimator is constructed to obtain disturbance estimations, without the priori information of vessel motion model dynamic parameters. The Nussbaum-gain function is inserted to alleviate the requirement on the control coefficient. A saturation dynamic filter is adopted to address the actuator constraint effect. By the fusion of the command filtered backstepping method, the adaptive disturbance rejection tracking controller is designed. The computational burden is reduced due to command filters to avoid the virtual stabilizing function differentiation. Stability analysis proves the vessel course trajectory tracking and the closed-loop steering stability. Numerical simulations on an unmanned surface vessel validate the adaptive course tracking approach. Highlights: No a priori knowledge of vessel dynamics and ocean disturbances is required. Actuator constraint is simultaneously addressed in the vessel autopilot design. Computational burden is reduced due to the introduction of command filter.